MongoDB performance tuning optimizing MongoDB databases and their applications - Harrison, Guy; Harrison, Michael (Apress, 2021)
Use this fast and complete guide to optimize the performance of MongoDB databases and the applications that depend on them. You will be able to turbo-charge the performance of your MongoDB applications to provide a better experience for your users, reduce your running costs, and avoid application growing pains. MongoDB is the world's most popular document database and the foundation for thousands of mission-critical applications. This book helps you get the best possible performance from MongoDB. MongoDB Performance Tuning takes a methodical and comprehensive approach to performance tuning that begins with application and schema design and goes on to cover optimization of code at all levels of an application. The book also explains how to configure MongoDB hardware and cluster configuration for optimal performance. The systematic approach in the book helps you treat the true causes of performance issues and get the best return on your tuning investment. Even when you're under pressure and don't know where to begin, simply follow the method in this book to set things right and get your MongoDB performance back on track. You will: Apply a methodical approach to MongoDB performance tuning Understand how to design an efficient MongoDB application Optimize MongoDB document design and indexing strategies Tune MongoDB queries, aggregation pipelines, and transactions Optimize MongoDB server resources: CPU, memory, disk Configure MongoDB Replica sets and Sharded clusters for optimal performance.
Includes index
Keywords: MongoDB; Database management; Bases de données; Gestion